Model Reciprocal Teaching Pada Pembelajaran IPA di Sekolah Dasar - Setiyawati, Enik - (Inovasi: Jurnal Diklat Keagamaan, 2022)
The purpose of this study was to describe the Reciprocal Teaching model in science learning in elementary schools. The research approach used is descriptive qualitative with a literature review. The data sources used in this article are from journals categorized as main sources and supporting sources in the span of 10 years (2012 to 2020). The research findings indicate that the Reciprocal Teaching model can be used as an alternative in the science learning process in elementary schools because it is an effective learning model with an understanding of empathy strategies, namely summarizing readings, asking questions, predicting advanced material, and clarifying difficult to reach terms. The use of the Reciprocal Teaching model in learning in elementary schools can improve student learning activities, science learning outcomes, critical thinking skills, science knowledge competencies, students' reading skills, students' communication skills, students' reading mastery, and student learning mastery.